A Rare Cause of Acute Hepatopancreatitis in a Nepalese Teen - Swastika Adhikari; Ashish Lal Shrestha; Sanjay Raj Thapa; Amrit Ghimire (Case Reports in Pediatrics)
Background. Acute pancreatitis (AP) coexisting with acute hepatitis (AH) in children is uncommon. Moreover, a single bacterial cause explaining both the complications is even rarer. Despite familiarity with the usual presentation of enteric fever, atypical presentations can go unnoticed. Case Presentation. A 16-year-old previously healthy male presented to the emergency unit with recurrent swinging pyrexia, abdominal symptoms, and jaundice for a week. Blood work-up revealed deranged liver function tests (LFTs) and elevated pancreatic enzymes. Further assessment with imaging made a diagnosis of AH and AP without necrosis. Blood culture positivity for Salmonella typhi eventually confirmed the diagnosis. Conclusion. This is an uncommon presentation of an infection that is fairly common in our part of globe. Nevertheless, early suspicion and recognition is the key to timely management. Regular follow-ups are required to pick complications up early.